Motion design and visual communication in the era of 'diffuse design' paradigm: analysis and evaluation of a didactic experiment. (23rd August 2022) - Maselli, Vincenzo; Panadisi, Giulia
Abstract: In recent years, co-creation and collaboration platforms to create and deliver new products and services have taken a step forward; this has led to the development of a new active involvement of users, who from co-designers have become independent designers, even if not experts. Co-design is dynamic and provides the tools to generate democratic design processes guided by the users themselves. The democratization of design tools is the premise for a new paradigm defined 'Diffuse Design' by Manzini (2015). This contribution explores the approaches of open design and open production with particular attention to the field of visual communication and the production of motion design artifacts. After an introduction to the co-design framework, the main open-production visual communication platforms are presented to offer an overview of the topic. Next, the potential of online platforms to enable non-designers to produce animated artifacts is explored by examining student projects in a motion design University course. The most significant outputs of the student experience are then described and critically analyzed. Finally, the conclusions investigate the different perspectives for reading the democratization of tools for creating visual artifacts and lay the foundations for future lines of research.